Antipsychotic polypharmacy and psychopharmacological prescription patterns in long stay psychiatry hospitalization: 1995-2009 comparison - Damián Gargoloff, Pedro (2022)
Objective: To identify changes of prescription patterns in long term psychiatric inpatients in 1995 and 2009. Material and Methods: Cross sectional comparative study of two one-day-census, (06/15/1995 and 12/14/2009) at the Hospital Neuropsiquiátrico Alejandro Korn, Argentina. Records of prescribed psychotropic agents to all patients in long stay wards were examined. Results: The number of hospitalized patients decreased 33% from 1995 (n=1048) to 2009 (n=698), with increases in male gender (44% a 57%) and hospitalizations lasting more than 20 years (29% a 40%). Schizophrenia remained as the most prevalent diagnosis followed by learning disabilities/mental retardation (45% and 27% in 1995, respectively, 44% and 33% in 2009). The average antipsychotic dosis in schizophrenia was almost the same, the equivalent of around 760 mg of chlorpromazine. Patients on antipsychotic doses above an equivalent of 1200 mg decreased from 28% to 23,9%. Around 80% of those with learning disabilities were prescribed antipsychotics on both census. Antipsychotic polypharmacy increased 6,7% in schizophrenia (61%) and decreased 12,6% in learning disabilities (45%), and 6,5% in all inpatients (49%). Haloperidol and levomepromazine were still the more frequently prescribed antipsychotics while the use of anticholinergic agents diminished in a 21%. Regarding sedatives, the use of benzodiazepines and promethazine increased (15% and 19% respectively), while around 35% in both census was still receiving levomepromazine. Discussion: The introduction of atypical antipsychotic was not followed by great improvements in the rational use of psychotropics drugs, except for less antipsychotic polypharmacy in learning disabilities and of anticholinergics in the general population. Conclusion: The increase in antipsychotic polypharmacy in schizophrenia and the continuous use of benzodiazepines highlight the need to bring the usual practice closer to the evidence provided by clinical research.